Visible-light-driven photocatalyst based on bonding of carbon nitride and anthraquinone as well as preparation method and application of visible-light-driven photocatalyst
The improved photocatalyst is formed by bonding the graphite phase carbon nitride with anthraquinone compounds through amide or ester-based chemical bonds, which solves the problem of insufficient catalyst activity and stability in the prior art, and achieves efficient hydrogen peroxide formation.
Patent Information
- Application Number
- CN202411542118.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
In the process of catalyzing the formation of hydrogen peroxide, the existing photocatalysts that combine carbon nitride with anthraquinone have poor activity and stability, resulting in a lower amount of hydrogen peroxide production.
The improved photocatalyst is formed by bonding the graphite phase semiconductor carbon nitride to the anthraquinone compound through an amide or ester-based chemical bond. This method introduces oxygen-containing functional groups into the carbon nitride triazine ring network structure, changes the oxygen adsorption activation site, and affects the electronic structure of the triazine ring through the conjugated structure, thereby improving the photocurrent density and charge transport path.
The selectivity of photocatalytic oxygen dual-electron reduction to produce hydrogen peroxide is significantly improved, and the efficient hydrogen peroxide preparation process is achieved, and the activity and stability of the catalyst have also been significantly improved.
Smart Images

Figure CN119456026A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic material preparation, and in particular to a visible light catalyst based on the bonding of carbon nitride and anthraquinone, and a preparation method and application thereof. Background Art
[0002] As a multifunctional chemical and green oxidant, hydrogen peroxide (H2O2) plays an important role in chemistry, printing, pharmaceuticals and other industrial fields. The main preparation methods include electrochemical preparation, alkaline hydrogen peroxide preparation, alcohol oxidation, direct hydrogen-oxygen combination, anthraquinone method, and barium heating in air to generate barium peroxide followed by sulfuric acid addition. At present, more than 95% of H2O2 is produced by the mature anthraquinone (AQ) process. AQ has excellent selectivity for H2O2 precipitation reaction and has a high H2O2 yield, but the overall process is complex and must consume a large amount of energy and organic solvents, which brings a huge burden to the environment. The hydrogenation and oxidation process and the working liquid recycling process of the anthraquinone method are optimized to convert the anthrone-type compounds in the working liquid into anthraquinone-type compounds, solving the problem of low regeneration efficiency in the existing process (CN 106829872 B). In the bubbling gas-liquid reaction equipment, the oxidation method is changed to integrate the gas-liquid reaction and the gas-liquid separation, thereby improving the reaction efficiency and the safety of the device (CN 111099563 B). In addition, mesoporous silicon materials are used in intermittent oxidation reaction vessels to pass a mixed atmosphere of hydrogen, oxygen and nitrogen, realizing a direct and highly selective hydrogen peroxide production process (CN 109289839 B). Electrocatalysts made of precious metals such as platinum, gold and palladium are used to realize electrochemical preparation of oxygen, and the selectivity of hydrogen peroxide can reach more than 95% (CN111617775 B). In the hydrogen peroxide synthesis process, the highly active hydrogenation process requires Au, Pd, Au-Pd and Pd-Pt precious metal catalysts, which are costly, require high equipment, and have low safety of direct O2 / H2 mixing. With the continuous research on the hydrogen peroxide preparation process, people are increasingly concerned about finding a greener, safer and more efficient process flow.
[0003] Heterogeneous photocatalysis technology has become a promising alternative due to its advantages of high efficiency, high selectivity and high cost performance. The photoreaction process only requires semiconductor photocatalysts, water, oxygen and ideal sunlight irradiation, without direct contact between hydrogen and oxygen. It has low requirements for production equipment, mild reaction conditions, high safety, non-toxicity and pollution-free, but has high requirements for the photocatalysts used. At present, the most studied non-metallic semiconductor catalyst for H2O2 production is polymerized carbon nitride (CN). The surface of carbon nitride has abundant CN=C units and is a typical reducing semiconductor photocatalyst. After reacting with oxygen, it is easy to form 1,4-endocyclic compounds, and selectively carry out two-electron reduction of 2e on the carbon / nitrogen-based reaction center.- In the process of generating hydrogen peroxide by ORR, it has a high kinetic advantage of converting solar energy into chemical energy, and is an excellent choice for realizing the photocatalytic synthesis of hydrogen peroxide.
[0004] Nitrogen-deficient carbon nitride nanosheets can be obtained by repeated calcination in a nitrogen atmosphere. The CN in the nanosheets is the sp 2 The hybridized N atoms form nitrogen vacancies, and the concentration of nitrogen defects can be controlled. The rate of photocatalytic H2O2 production can reach 2.80-4.98 mmol·g -1 ·h -1 (CN 113830742 A). The Schiff base reaction is used to generate a carbon-nitrogen double bond between the aldehyde group in pyridine-2-carboxaldehyde and the amino group in g-C3N4. The multi-electron delocalization system of the pyridine ring is used to form a directional electric field in the molecule, inducing the separation of photogenerated electrons and holes, thereby improving the utilization efficiency of solar energy. The hydrogen peroxide production can reach 637 μmol / L, which is 2.04 times that of undoped pyridine-2-carboxaldehyde (CN 115845896A). The wide structural band gap, low surface area and porosity of carbon nitride itself, the π-conjugated polymerization structure inside g-C3N4 and the interlayer π-π stacking conjugation lead to a high probability of carrier recombination, which limits its development in the field of hydrogen peroxide production.
[0005] In addition, there are some other prior art documents 1-8 that have also tried to combine carbon nitride and anthraquinone, but they have different technical problems:
[0006] [1] U. Alam, A. Pandey, N. Verma, An anthraquinone-integrated S-scheme-based NiTiO3-g-C3N4 composite with enhanced hydrogen production activity, Int. J. Hydrogen Energy. 48 (2023) 2532-2541. The authors describe the preparation of composite materials of carbon nitride and anthraquinone derivatives by simple physical solvent mixing. Although the operation is simple, this physical solvent mixing method fails to achieve efficient chemical bonding, resulting in poor catalyst activity and stability and low hydrogen peroxide production.
[0007] [2]W.Liu,R.Xu,Y.Wang,N.Huang,T.Shimada,L.Ye,AQ-coupled few-layered g-C3N4 nanoplates obtained by one-step mechanochemical treatment for efficientvisible-light photocatalytic H2O2 production,Int.J.Hydrogen Energy.47(2022)16005-16013. The samples were prepared by mechanical mixing and reacted under specific conditions. Although the method is simple, it failed to effectively improve the activity and stability of the catalyst, and the amount of hydrogen peroxide produced was still low.
[0008] [3] A. Torres-Pinto, H. Boumeriame, CG Silva, JL Faria, MT Silva, Boosting Carbon Nitride Photoactivity by Metal-Free Functionalization for Selective H2O2 Synthesis under Visible Light, ACS Sustainable Chem. Eng. 11 (2023) 894-909. describes the preparation of carbon nitride by a simple hydrothermal treatment followed by coupling with anthraquinone derivatives. Despite the simplicity of the operation, efficient chemical bonding was not achieved, resulting in poor catalyst activity and stability and low hydrogen peroxide production.
[0009] [4] M.Gu, D.Lee, J.Mun, D.Kim, H.Cho, B.Kim, W.Kim, G.Lee, B.Kim, H.Kim, Solar-to-hydrogen peroxide conversion of photocatalytic carbon dots with anthraquinone: Unveiling the dual role of surface functionalities, Appl. Catal. BEnviron. 312 (2022) 121379. The paper describes the preparation of catalysts by combining carbon dots with anthraquinone derivatives. Although carbon dots have good optical properties, their binding efficiency with anthraquinone derivatives is low and the synthesis process is complicated, making it difficult to apply them on a large scale.
[0010] [5] H. Kim, Y. Choi, S. Hu, W. Choi, J. Kim, Photocatalytic hydrogen peroxide production by anthraquinone-augmented polymeric carbon nitride, Appl. Catal. BEnviron. 229 (2018) 121-129. Carbon nitride was combined with anthraquinone derivatives by solvent-free physical coupling. Although this method is simple, the physical coupling method cannot obtain effective conjugated plane links, fails to effectively improve the activity of the catalyst, and the amount of hydrogen peroxide produced is limited.
[0011] [6]C.Chu, Q.Zhu, Z.Pan, S.Gupta, D.Huang, Y.Du, S.Weon, Y.Wu, C.Muhich, E.Stavitski, K.Domen, J.Kim, Spatially separating redox centers on 2Dcarbonnitride with cobalt single atom for photocatalytic H2O2 production,PNAS.117(2020)6376-6382.
[0012] [7] F. Yu, Y. Wang, H. Ma, G. Dong, Enhancing the yield of hydrogen peroxide and phenol degradation via a synergistic effect of photoelectrocatalysis using a g-C3N4 / ACF electrode, Int. J. Hydrogen Energy. 43 (2018) 19500-19509.
[0013] [8] A method for forming an amide bond, CN 101235078 B; describes the general principle of forming an amide bond through carboxylic acid and free amine or ammonium salt, but the organic covalent bonding method applied between the amino group of the polymer macromolecular structure and anthraquinone-2-carboxylic acid still needs further exploration.
[0014] The following table summarizes the above 8 known documents:
[0015]
[0016]
[0017] In summary, references 1-7 are other known methods for combining AQ derivatives with carbon nitride reported in the literature, including physical coupling and chemical coupling. In the above methods, the final combination of AQ and CN is an ionic bond, and no chemical bond is formed. The difference is that there is no obvious peak attributable to the amide bond in the XRD and infrared spectra reported in the literature, there is no covalent bond preparation, and the yield of hydrogen peroxide is low.
[0018] Therefore, optimizing the structure of carbon nitride photocatalysts and improving their photocatalytic efficiency are important current research directions. Summary of the invention
[0019] The purpose of the present invention is to solve the shortcomings in the field of existing photocatalyst structure optimization, and to provide a method for preparing an improved semiconductor carbon nitride catalyst by organically bonding anthraquinone-based molecular composite catalysts. The photocatalyst is prepared by chemically bonding anthraquinone and graphite phase carbon nitride (g-C3N4), and an oxygen-containing functional group carbonyl is introduced into the carbon nitride triazine ring network structure to change the oxygen adsorption activation site. At the same time, the anthraquinone structure linked to the edge affects the triazine ring electronic structure through the conjugated structure, the photocurrent density is increased, the charge transfer path is changed, and the selectivity of the photocatalytic oxygen two-electron reduction to generate hydrogen peroxide is enhanced. A highly efficient preparation process of hydrogen peroxide is achieved.
[0020] The first aspect of the present invention is to protect a method for preparing a visible light catalyst based on the bonding of carbon nitride and anthraquinone: a composite organic semiconductor catalyst comprising a graphite phase semiconductor carbon nitride and anthraquinone compounds bonded by an amide (NH-C=O) or ester (COC=O) chemical bond, and the specific preparation method is as follows ( Figure 7 ):
[0021] Step (1): preparing a carbon nitride precursor: using at least one of dicyandiamide, melamine, thiourea, urea, ammonium thiocyanate, ammonium thiocyanate and ammonium sulfate, ammonium thiocyanate and ammonium thiosulfate, ammonium thiocyanate, ammonium thiosulfate and ammonium sulfate as a precursor; heating at normal pressure, controlling the heating rate at 2 to 20°C / min, raising the temperature to 450 to 650°C, and maintaining the temperature for 1 to 5 hours to obtain a graphite phase semiconductor carbon nitride (g-C3N4) having an edge amino group or a cyano group;
[0022] Wherein, in the case of obtaining edge cyano groups, ammonium chloride is additionally added and physically ground and mixed with the above-mentioned precursor materials;
[0023] Step (2): In the case of forming an ester group (COC=O) chemical bond connection, the g-C3N4 containing a cyano group obtained in step (1) is additionally subjected to an oxidative modification treatment to convert it into a hydroxyl group (C-OH);
[0024] Step (3): converting the anthraquinone compound containing a carboxylic acid, carboxylic acid ester or amide substituent into a form containing an acyl halide functional group;
[0025] Step (4): according to the selected chemical bond type, the amino group-containing g-C3N4 directly obtained in step (1) (for amide bond) or the hydroxyl group-containing g-C3N4 (for ester bond) after oxidation modification in step (2) and the anthraquinone compound containing acyl halide functional group prepared in step (3) are stirred for 1 to 24 hours at normal pressure of 10 to 60° C. and oxygen atmosphere in the presence of an organic base or an inorganic base acid-binding agent; after the reaction is completed, the product is collected by solid-liquid centrifugation, washed with ethanol and water, and finally vacuum dried at 30 to 95° C., thereby obtaining a g-C3N4 photocatalyst bonded to anthraquinone compounds through an amide bond or an ester bond, respectively.
[0026] For the technical solution described above, in a further preferred case, the irradiation condition is that visible light or ultraviolet light can react to obtain hydrogen peroxide; more preferably, a white light source such as a xenon lamp or a tungsten halogen lamp with a wavelength of 400 to 700 nm, and a light intensity of 1000 to 2000 W / m 2 Under the condition of continuous illumination for 4h to 16h; the optimal illumination time is 8-10h, and the hydrogen peroxide production increases first and then decreases;
[0027] For the technical solution described above, in a further preferred case, in step (2), the oxidation catalyst in the oxidation process is selected from at least one of the following: hydrogen peroxide, ammonium persulfate, ammonium iodate, perchloric acid and benzoyl peroxide with a concentration of 1 to 2 eq, and citric acid with a concentration of 0 to 1.5 eq (preferably 0.5 to 1 eq); further preferably, the oxidant is a 34 wt% H2O2 solution, and citric acid has the effect of promoting the reaction, and the reaction can also be carried out without adding it, and the reaction effect is enhanced by adding it;
[0028] For the technical solution described above, in a further preferred case, the anthraquinone compound containing carboxylic acid, carboxylic acid ester, or amide substituent is mainly selected from one of the following: anthraquinone-1-carboxylic acid, anthraquinone-2-carboxylic acid, anthraquinone-2,6-dicarboxylic acid, anthraquinone-2,3-dicarboxylic acid, 4,5-dicarboxyanthraquinone, 1,4-anthraquinone-2,3-dicarboxylic acid, and all anthraquinone compounds containing a carboxyl group (-COOH); 4,5-dihydroxyanthraquinone-2-carboxylic acid, 1-aminoanthraquinone-2-carboxylic acid, anthraquinone-2,3-dicarboxylic acid diethyl ester, 4,5-diacetylanthraquinone, 4,5-diamideanthraquinone, 1,4-anthraquinone-2,3-diamide, and all anthraquinone compounds containing a carboxyl group (-COOM);
[0029] For the technical scheme described above, in a further preferred case, the preparation method of the anthraquinone compound containing an acyl halide functional group comprises 1 to 2 eq of sulfoxide chloride, oxalyl chloride, phosphorus trichloride, phosphorus oxychloride, etc. (among which phosphorus oxychloride has the best effect) of an acyl halide reagent commonly used in the acyl halide method, and 0.1 to 0.2 eq of pyridine or 4-dimethylaminopyridine (DMAP) is added during the process to promote the formation of acyl halide, and the reaction is carried out under normal pressure at a temperature of 10 to 60°C;
[0030] For the technical solution described above, in a further preferred case, the obtained carbon nitride reacts with anthraquinone containing an acyl halide functional group under the action of an acid binding agent, including an inorganic base acid binding agent selected from one of the following: ammonia water, sodium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide, etc., and an organic base acid binding agent selected from one of the following: triethylamine, ammonium acetate, acetamide, phenylethylamine hydrochloride, N,N-diisopropylethylamine (DIEA), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), etc., among which triethylamine and sodium hydroxide have the best combination effect.
[0031] For the technical solution described above, in a further preferred case, the stirring temperature in step (4) is preferably 10 to 40° C., or near room temperature; and the reaction can be carried out for 6 to 24 hours.
[0032] Another aspect of the present invention is to protect the visible light photocatalyst based on the bonding of carbon nitride and anthraquinone prepared by the above method.
[0033] Another aspect of the present invention is to protect the application of the visible light photocatalyst based on the bonding of carbon nitride and anthraquinone, and the specific application fields include:
[0034] Hydrogen peroxide production: replace traditional chemical preparation methods, reduce energy consumption and environmental pollution.
[0035] Wastewater treatment: used to treat organic pollutants in industrial wastewater, improve treatment efficiency and reduce secondary pollution.
[0036] Used to prepare high-purity hydrogen peroxide to meet the demand for pharmaceutical-grade hydrogen peroxide and electronic-grade hydrogen peroxide products.
[0037] For the technical scheme described above, further preferred is the method for preparing hydrogen peroxide by catalytic oxidation of low-carbon alcohols and water by visible light activated molecular oxygen, which comprises the following steps: mixing water and / or C2-C6 low-carbon alcohols with 4-30 wt % of the above-mentioned visible light catalyst based on carbon nitride and anthraquinone bonding, in an oxygen atmosphere, at a reaction temperature of 15-45° C., and irradiating with ultraviolet light or visible light for a certain period of time to obtain hydrogen peroxide.
[0038] For the technical solution described above, in a further preferred case, the C2-C6 low-carbon alcohol is selected from methanol, ethanol, isopropanol, propanol, ethylene glycol and 1,2-propylene glycol; among them, pure ethanol solution has the best effect. In the solar-driven two-electron reduction of molecular oxygen, it is hoped that the highest H2O2 yield can be obtained with the least organic sacrificial agent. The CN-AQ-3 catalyst in this patent also has a higher H2O2 yield when the amount of organic sacrificial agent is reduced.
[0039] For the technical solution described above, in a further preferred case, the mixing volume ratio of water to C2-C6 low-carbon alcohol is 0:1 to 1:1.
[0040] For the technical scheme described above, in a further preferred case, the C2-C6 low-carbon alcohol is selected from one of the following: ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, isopentanol, neopentyl alcohol, and n-hexanol.
[0041] For the technical scheme described above, in a further preferred case, the reaction is carried out at room temperature, the reaction conditions are mild, and a higher or lower temperature can obtain a better H2O2 yield.
[0042] Beneficial effects:
[0043] The process proposed by the present invention uses a photocatalyst with excellent performance and stable recycling. The catalyst also has a simple separation process, providing an efficient and low-cost solution for preparing high-concentration and high-purity hydrogen peroxide. The entire production process is simple and easy to control, with low energy consumption, fully meeting the standards of green and clean production, not only reducing production costs, but also very suitable for large-scale industrial application and promotion, showing significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 X-ray diffraction spectra of the carbon nitride photocatalyst CN-AQ-3 obtained in Example and the control blank samples CN, AQ, and CN+AQ.
[0045] Figure 2 Fourier transform infrared spectra of the carbon nitride photocatalyst CN-AQ-3 obtained in Example and the control blank samples CN, AQ, and CN+AQ.
[0046] Figure 3 These are scanning electron microscope images and high-resolution transmission electron microscope images of the carbon nitride photocatalyst CN-AQ-3 obtained in Example.
[0047] Figure 4 This is a comparison chart of the yield of H2O2 generated by visible light of all carbon nitride and anthraquinone composite organic semiconductor photocatalysts CN-AQ in the examples.
[0048] Figure 5 Comparison of the amount of H2O2 generated by the composite organic semiconductor photocatalyst CN-B-AQ under visible light and the amount of hydrogen peroxide generated by the control experimental group samples CN, CN+AQ-COOH, CN+AQ, CN-AQ, T-AQ, and CN-GO.
[0049] Figure 6 A comparison chart of the amount of hydrogen peroxide generated by the CN-3 sample involved in the preparation process of the composite organic semiconductor photocatalyst CN-AQ-3 in the example and the control sample obtained by other modification methods such as mixed salt co-dissolution method, metal ion doping method, and pyrolysis of other types of precursors mixed with NH4Cl.
[0050] Figure 7 A diagram showing a method for preparing the catalyst of the present invention. DETAILED DESCRIPTION
[0051] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0052] Embodiment 1:
[0053] Catalyst preparation:
[0054] Step (1): 10 g of melamine was placed in a quartz boat, placed in a tube furnace at room temperature, heated to 550° C. at a rate of 3° C. / min, kept at this temperature for 3 h, and then cooled to room temperature to obtain 2 to 3 g of carbon nitride CN-1;
[0055] Step (2): 2 mmol of anthraquinone-2-carboxylic acid compound, 0.1 mmol of pyridine, 2 mmol of POCl3, and 20 ml of anhydrous dichloromethane as the reaction solvent were mixed in a round-bottom glass reactor at normal pressure and 25° C., and stirred for 6 h to prepare an anthraquinone compound AQ-1 containing an acyl halide functional group;
[0056] Step (3): 0.6 g of carbon nitride CN-1 obtained in step (1) and anthraquinone compound AQ-1 obtained in step (2) are mixed, and the mixture is reacted in the presence of 0.3 mmol 99.0% triethylamine and 20 ml dichloromethane as the reaction solvent to obtain a suspension of the mixture;
[0057] Step (4): stirring the mixture suspension obtained in step (3) at 25° C. and oxygen atmosphere for 12 h, and after the reaction is completed, centrifuging at 1200 r / min for 15 min, and vacuum drying the lower layer of solid at 0.04 kPa and 60° C. to obtain visible light catalyst CN-AQ-1;
[0058] Step (5): Mix 3 ml of ethanol and 10 mg of visible light catalyst CN-AQ-1, and after adsorption equilibrium for 2 hours in a saturated oxygen atmosphere at 25°C, react in a photoreactor under 10 W white light irradiation while maintaining the reaction temperature at 25°C for 8 hours. Centrifuge the obtained reaction solution at 1200 r / min for 10 minutes, take the supernatant and calibrate it by iodine titration. The concentration of hydrogen peroxide H2O2 is 1.48 wt%.
[0059] Embodiment 2:
[0060] Catalyst preparation:
[0061] Step (1): 10 g of thiourea is placed in a quartz boat, placed in a tube furnace at room temperature, heated to 520° C. at a rate of 5° C. / min, kept at this temperature for 2 h, and then cooled to room temperature to obtain 1 to 2 g of carbon nitride CN-2;
[0062] Step (2): 2 mmol of anthraquinone-2-carboxylic acid compound, 0.3 mmol of pyridine and 2.5 mmol of POCl3 were mixed in a round-bottom glass reactor at normal pressure and 25°C, the reaction solvent was 20 ml of dichloromethane, and stirred for 4 h to prepare an anthraquinone compound AQ-2 containing an acyl halide functional group;
[0063] Step (3): 0.4 g of carbon nitride CN-2 obtained in step (1) and anthraquinone compound AQ-2 obtained in step (2) are mixed, and a mixture suspension is obtained under the action of 2 mmol 0.1 g / ml NaOH and a solvent of 20 ml dichloromethane;
[0064] Step (4): stirring the mixture suspension obtained in step (3) at 25° C. and oxygen atmosphere for 12 h, and after the reaction is completed, centrifuging at 1200 r / min for 15 min, and vacuum drying the lower layer of solid at 0.04 kPa and 50° C. to obtain visible light catalyst CN-AQ-2;
[0065] Step (5): Mix 3 ml of ethanol and 10 mg of visible light catalyst CN-AQ-2, and after adsorption equilibrium for 2 hours in a saturated oxygen atmosphere, react in a parallel light reactor for 8 hours under 15 W white light irradiation while maintaining the reaction temperature at 20° C. The obtained reaction solution is centrifuged at 1200 r / min for 10 minutes, and the supernatant is taken for iodine titration to determine the hydrogen peroxide H2O2 concentration to be 2.04 wt%.
[0066] Embodiment 3:
[0067] Catalyst preparation:
[0068] Step (1): 10 g of thiourea and 2 g of ammonium chloride are placed in a quartz boat, placed in a tube furnace at room temperature, heated to 550° C. at a rate of 5° C. / min, kept at this temperature for 3 h, and then cooled to room temperature to obtain 1 to 2 g of carbon nitride CN-3;
[0069] Step (2): 2.5 mmol g of anthraquinone-2-carboxylic acid compound, 0.25 mmol 4-dimethylaminopyridine, and 2 mmol POCl3 were mixed in a round-bottom glass reactor at normal pressure and 25° C., the reaction solvent was 20 ml of dichloromethane, and stirred for 8 h to prepare an anthraquinone compound AQ-3 containing an acyl halide functional group;
[0070] Step (3): 0.45 g of carbon nitride CN-3 obtained in step (1), 0.2 g of citric acid, 0.2 ml of 34% H2O2 and the anthraquinone compound AQ-3 obtained in step (2) are mixed, and the mixture is reacted in the presence of 0.2 mmol of 99.0% triethylamine and 20 ml of dichloromethane as the reaction solvent to obtain a suspension of the mixture;
[0071] Step (4): stirring the mixture suspension obtained in step (3) at 25° C. and oxygen atmosphere for 12 h, and after the reaction is completed, centrifuging at 1200 r / min for 15 min, and vacuum drying the lower layer of solid at 0.04 kPa and 60° C. to obtain visible light catalyst CN-AQ-3;
[0072] Step (5): Mix 3 ml of ethanol and 10 mg of visible light catalyst CN-AQ-3, and after adsorption equilibrium for 2 hours in a saturated oxygen atmosphere, irradiate with 10 W white light, maintain the reaction temperature at 25° C., and react in a parallel light reactor for 8 hours. Centrifuge the obtained reaction solution at 1200 r / min for 10 minutes, take the supernatant and calibrate it with iodine titration to determine the hydrogen peroxide H2O2 concentration of 4.03 wt%.
[0073] Embodiment 4:
[0074] Catalyst preparation: Step (1): 10 g of thiourea and 2 g of ammonium chloride were placed in a quartz boat, placed in a tube furnace at room temperature, heated to 550° C. at a rate of 3° C. / min, kept at this temperature for 3 h, and then cooled to room temperature to obtain 1 to 2 g of carbon nitride CN-4;
[0075] Step (2): 3 mmol of anthraquinone-2,6-dicarboxylic acid compound, 0.3 mmol of 4-dimethylaminopyridine and 2 mmol of POCl3 were mixed in a round-bottom glass reactor at normal pressure and 25°C, the reaction solvent was 20 ml of anhydrous dichloromethane, and stirred for 8 h to prepare an anthraquinone compound AQ-4 containing an acyl halide functional group;
[0076] Step (3): 0.6 g of carbon nitride CN-4 obtained in step (1), 0.2 g of citric acid, 0.1 g of ammonium iodate and the anthraquinone compound AQ-4 obtained in step (2) are mixed, and the mixture is reacted in the presence of 1 mmol 99.0% triethylamine and 20 ml of dichloromethane as the reaction solvent to obtain a suspension of the mixture;
[0077] Step (4): stirring the mixture suspension obtained in step (3) at 25° C. and oxygen atmosphere for 12 h, and after the reaction is completed, centrifuging at 1200 r / min for 15 min, and vacuum drying the lower layer of solid at 0.04 kPa and 50° C. to obtain visible light catalyst CN-AQ-4;
[0078] Step (5): Mix 2 ml of ethanol and 1 ml of water with 11 mg of visible light photocatalyst CN-AQ-4, and after adsorption equilibrium for 2 h in a saturated oxygen atmosphere, irradiate with 10 W white light, maintain the reaction temperature at 25 ° C, and react in a photoreactor for 9 h. The obtained reaction solution is centrifuged at 1200 r / min for 10 min, and the supernatant is taken for iodine titration to determine the hydrogen peroxide H2O2 concentration of 1.94 wt%.
[0079] Embodiment 5:
[0080] Catalyst preparation: Step (1): 5 g of thiourea and 5 g of melamine were placed in a quartz boat, placed in a tube furnace at room temperature, heated to 500 °C at a rate of 4 °C / min, kept at constant temperature for 2 h, and then cooled to room temperature to obtain 1-2 g of carbon nitride CN-5;
[0081] Step (2): 2 mmol of anthraquinone-2-carboxylic acid compound, 0.1 mmol of 4-dimethylaminopyridine and 1 mmol of POCl3 were mixed in a round-bottom glass reactor at normal pressure and 25°C, the reaction solvent was 20 ml of dichloromethane, and stirred for 7 h to prepare an anthraquinone compound AQ-5 containing an acyl halide functional group;
[0082] Step (3): 0.4 g of carbon nitride CN-5 obtained in step (1) and anthraquinone compound AQ-5 obtained in step (2) are mixed, and the mixture is reacted in the presence of 2 mmol 0.1 g / ml NaOH in a reaction solvent of 20 ml dichloromethane to obtain a suspension of the mixture;
[0083] Step (4): stirring the mixture suspension obtained in step (3) at 25° C. and oxygen atmosphere for 12 h, and after the reaction is completed, centrifuging at 1200 r / min for 15 min, and vacuum drying the lower layer of solid at 0.04 kPa and 50° C. to obtain visible light catalyst CN-AQ-5;
[0084] Step (5): 3 ml of isopropanol and 10 mg of visible light catalyst CN-AQ-5 were mixed, and after adsorption equilibrium for 2 hours in a saturated oxygen atmosphere, the reaction temperature was maintained at 15° C. and the reaction was carried out in a parallel light reactor for 8 hours under 10 W white light irradiation. The obtained reaction solution was centrifuged at 1200 r / min for 10 minutes, and the supernatant was calibrated by iodine titration to determine that the concentration of hydrogen peroxide H2O2 was 0.86 wt%. Although the yield was lower than that of other samples such as Example 3, it was still higher than the hydrogen peroxide output of current non-metallic semiconductor catalysts.
[0085] Embodiment 6:
[0086] Catalyst preparation: Step (1): 10 g of thiourea and 2 g of ammonium chloride were placed in a quartz boat, placed in a tube furnace at room temperature, heated to 550° C. at a rate of 3° C. / min, kept at this temperature for 3 h, and then cooled to room temperature to obtain 1 to 2 g of carbon nitride CN-6;
[0087] Step (2): 3 mmol of 1,8-dihydroxy-3-carboxyanthraquinone compound, 0.1 mmol of 4-dimethylaminopyridine and 1.5 mmol of POCl3 were mixed in a round-bottom glass reactor at normal pressure and 25°C, the reaction solvent was 20 ml of dichloromethane, and stirred for 8 h to prepare an anthraquinone compound AQ-6 containing an acyl halide functional group;
[0088] Step (3): 0.65 g of carbon nitride CN-6 obtained in step (1) and anthraquinone compound AQ-6 obtained in step (2) are mixed, and the mixture is reacted in the presence of 2 mmol 0.1 g / ml NaOH in a reaction solvent of 20 ml dichloromethane to obtain a suspension of the mixture;
[0089] Step (4): stirring the mixture suspension obtained in step (3) at 25° C. and oxygen atmosphere for 14 h, and after the reaction is completed, centrifuging at 1200 r / min for 15 min, and vacuum drying the lower layer of solid at 0.02 kPa and 60° C. to obtain visible light photocatalyst CN-AQ-6;
[0090] Step (5): 2 ml of ethanol, 1 ml of water and 15 mg of visible light photocatalyst CN-AQ-6 were mixed, and after adsorption equilibrium for 2 h in a saturated oxygen atmosphere, the reaction temperature was maintained at 30° C. and the reaction was carried out in a parallel light reactor under 10 W white light irradiation for 10 h. The obtained reaction solution was centrifuged at 1200 r / min for 10 min, and the supernatant was taken for iodine titration to determine the concentration of hydrogen peroxide H2O2 to be 1.02 wt%. Although the yield was lower than that of other samples such as Example 3, it was still higher than the hydrogen peroxide output of current non-metallic semiconductor catalysts.
[0091] Distinguishing features of Examples 1-6
[0092]
[0093]
[0094] The differences between the embodiments and their impact on the results can be seen from the analysis of the above table:
[0095] 1. Raw materials and pyrolysis conditions
[0096] Examples 3 and 4 used thiourea and ammonium chloride, but the hydrogen peroxide concentration in Example 3 was the highest (4.03 wt %), which may be because citric acid and 34% H2O2 were added in Example 3, and these additives promoted the activity of the catalyst.
[0097] Example 1 uses melamine, and the hydrogen peroxide concentration is 1.48 wt %, which is relatively low.
[0098] Example 5 uses thiourea and melamine, and the hydrogen peroxide concentration is the lowest (0.86 wt %), which may be because the addition of melamine affects the performance of the catalyst.
[0099] Example 2 used thiourea and the hydrogen peroxide concentration was 2.04 wt %, which was relatively high.
[0100] Impact: Different raw materials and pyrolysis conditions directly affect the structure and properties of carbon nitride, which in turn affects the activity of the catalyst.
[0101] 2. Preparation of Anthraquinone Compounds
[0102] Example 3 used 2.5 mmol anthraquinone-2-carboxylic acid and 0.25 mmol 4-dimethylaminopyridine, and had the highest hydrogen peroxide concentration (4.03 wt%).
[0103] Example 4 used 3 mmol of anthraquinone-2,6-dicarboxylic acid and 0.3 mmol of 4-dimethylaminopyridine, and the hydrogen peroxide concentration was 1.94 wt %.
[0104] Example 6 used 3 mmol of 1,8-dihydroxy-3-carboxyanthraquinone and 0.1 mmol of 4-dimethylaminopyridine, and the hydrogen peroxide concentration was 1.02 wt %.
[0105] Example 2 used 2 mmol of anthraquinone-2-carboxylic acid and 0.3 mmol of pyridine, and the hydrogen peroxide concentration was 2.04 wt%.
[0106] Impact: The type and amount of different anthraquinone compounds and their auxiliary reagents significantly affect the activity of the catalyst. The combination of 2.5mmol anthraquinone-2-carboxylic acid and 0.25mmol 4-dimethylaminopyridine performs best.
[0107] 3. Preparation of Mixture Suspension
[0108] Example 3 added citric acid and 34% H2O2, and had the highest hydrogen peroxide concentration (4.03 wt%).
[0109] Example 4: Citric acid and ammonium iodate were added, and the hydrogen peroxide concentration was 1.94 wt%.
[0110] Example 2 used NaOH and the hydrogen peroxide concentration was 2.04 wt %.
[0111] Example 6 used NaOH and the hydrogen peroxide concentration was 1.02 wt %.
[0112] Effect: The type and amount of additives have a significant effect on the activity of the catalyst. The addition of citric acid and 34% H2O2 significantly increased the activity of the catalyst.
[0113] 4. Reaction conditions
[0114] The reaction conditions of Example 3 and Example 4 are similar, both are 10W white light, 25°C, but the reaction time of Example 3 is 8h, while that of Example 4 is 9h, which may be because a longer reaction time is helpful to increase the generation of hydrogen peroxide.
[0115] The reaction temperature of Example 6 was 30° C., and the hydrogen peroxide concentration was 1.02 wt %, which was relatively low.
[0116] The reaction temperature of Example 5 was 15° C., and the hydrogen peroxide concentration was the lowest (0.86 wt %).
[0117] Impact: Reaction time and temperature have a certain impact on the formation of hydrogen peroxide. Longer reaction time helps to increase the formation of hydrogen peroxide.
[0118] Different control groups
[0119] CN: A quartz boat containing 10 g of melamine was heated to 550° C. in a tube furnace under air atmosphere and maintained at this temperature for 3 h, followed by natural cooling to obtain carbon nitride (CN), and 0.4 g of CN was taken for experimental testing.
[0120] CN+AQ-COOH: 0.4 g CN and 2 mmol anthraquinone-2-carboxylic acid AQ-COOH were directly physically mixed to obtain the CN+AQ-COOH.
[0121] CN+AQ: 0.4 g CN and 2 mmol anthraquinone AQ were directly physically mixed to obtain the CN+AQ.
[0122] CN-GO: CN (0.4 g), triethylamine (0.2 mmol 99%) as an acid complexing agent, 4-dimethylaminopyridine (0.25 mmol) as a catalyst, phosphorus oxychloride (2 mmol) as a coupling agent, and anhydrous dichloromethane solvent (20 ml) were reacted under an oxygen atmosphere for 24 h at room temperature and pressure. The reaction solution was centrifuged and dried to obtain a CN-GO catalyst sample.
[0123] CN-AQ: CN (40 mg), anthraquinone-2-carboxylic acid (2 mmol), triethylamine (0.2 mmol 99%)), catalyst pyridine (0.25 mmol), coupling agent phosphorus oxychloride (2 mmol) and anhydrous dichloromethane solvent (20 ml) were reacted under air atmosphere for 24 h at room temperature and pressure. The reaction solution was centrifuged and dried to obtain a CN-B-AQ catalyst sample.
[0124] T-AQ: CN-T (40 mg), anthraquinone-2-carboxylic acid (2 mmol), triethylamine (0.2 mmol 99%)), catalyst pyridine (0.25 mmol), coupling agent phosphorus oxychloride (2 mmol) and anhydrous dichloromethane solvent (20 ml) were reacted in an oxygen atmosphere for 24 hours at room temperature and pressure. The solution after the reaction was centrifuged and dried to obtain the CN-B-AQ catalyst sample. Among them, CN-T was synthesized by heating 10 grams of melamine to 400°C in a tube furnace, keeping it for 2 hours and then cooling it naturally. (The characteristic structure of carbon nitride is not fully formed)
[0125] The product prepared in Example 1-6 is abbreviated as CN-B-AQ for the convenience of subsequent description;
[0126] The results of the above different control group experiments show that the H2O2 concentration is lower than that of CN-B-AQ (2.56wt%), indicating that the excellent hydrogen peroxide generation of CN-B-AQ is derived from the organic combination of anthraquinone molecules and the introduction of oxygen functional groups (carbonyl C=O) into the carbon nitride structure. By changing the synthesis atmosphere conditions (O2), these factors jointly promote the efficient synthesis of H2O2, and each element plays an indispensable role, namely the oxygen atmosphere, the carbon nitride structure, and the organic covalent bonding process of AQ-COOH and carbon nitride.
[0127] Figure 1 The X-ray diffraction spectra of the carbon nitride photocatalyst CN-AQ-3 obtained in the example and the control blank samples CN, AQ, and CN+AQ. The crystal structure of the catalyst was characterized by X-ray diffractometer (XRD). In all samples, the sharp characteristic peak (002) at 27.3° is the accumulation of conjugated aromatic compounds, while the peak (100) at 12.7° is attributed to the regular order within the 3-s-triazine unit plane ( Figure 1 ), indicating the formation of g-C3N4. It is worth noting that the (100) diffraction peak intensity of the catalyst sample CN-AQ-3 is significantly higher than that of CN, AQ and CN+AQ, and the peak position is slightly shifted to the left. This peak position does not correspond to the new peak introduced by the binding of AQ molecules, indicating that this novel oxidative binding method of AQ molecules enhances the interlayer interaction of g-C3N4 molecules, resulting in a new arrangement of the triazine ring network in the crystal structure. Compared with CN, AQ and CN+AQ, the (002) characteristic peak of the CN-AQ-3 sample is significantly shifted to a higher diffraction angle, which may be due to the formation of defects in the g-C3N4 framework, reducing the interlayer spacing of g-C3N4, thereby causing the angular displacement of the (002) characteristic peak. Compared with CN+AQ, the (002) diffraction peak of CN-AQ-3 is reduced, and a weak diffraction peak appears, indicating that the AQ molecule has changed the crystal structure of g-C3N4. In addition, the comparison of the XRD diffraction peaks of CN-AQ-3 with those of AQ and CN + AQ showed that, except for the peaks belonging to CN, the other peaks could be attributed to the AQ molecules, further confirming the successful binding of g-C3N4 with AQ.
[0128] Figure 2 The Fourier transform infrared spectra of the carbon nitride photocatalyst CN-AQ-3 obtained in the example and the control blank samples CN, AQ, and CN+AQ are shown. In the FTIR spectrum of CN-AQ-3, the characteristic peaks of AQ show similarity with the vibrations related to the aromatic ring and triazine ring of CN, resulting in the overlap of diffraction peaks. Compared with the FTIR spectra of AQ and CN+AQ, the peaks at 700 cm -1 The peaks observed at 830–1000 cm -1 1200-1500cm -1 and 3000-3400cm -1 The peak intensity increase in the range can be attributed to the presence of AQ, and its intensity is significantly higher than that of the control sample CN catalyst. In the CN-AQ-3 catalyst containing AQ, 810 cm -1 1140-1710cm -1 and 3000-3400cm -1 The peak intensity at is significantly higher than that of the CN-O modified g-C3N4 catalyst. The disappearance of the cyanide structure peak indicates that the oxidation modification site and the AQ binding site are located at the edge of the cyanide (-C≡N) group. Figure 2 As shown, 1025cm -1 and 1800cm -1The new peaks at are attributed to the presence of COC and C=O groups. The binding mode between CN-O and AQ may involve ester (-CO-CO-) bonding, which enhances electron transfer compared to most amide chains and may improve electronic conductivity due to increased oxygen doping.
[0129] Figure 3 The scanning electron microscope image and high-resolution transmission electron microscope image of the carbon nitride photocatalyst CN-AQ-3 obtained in Example 1 are shown in Figure 2. The prepared photocatalyst CN-AQ-3 was characterized by transmission electron microscopy (TEM), and its crystal phase was carefully characterized by high-resolution electron microscopy ( Figure 3 ). In the electron diffraction image and transmission electron diffraction image of CN-AQ-3, the CN-AQ-3 sample exhibited a nanosheet structure with a silk-thin surface. The CN-AQ-3 sample had a higher photocatalytic activity per unit surface area. The unique morphological structure of the CN-AQ-3 catalyst sample contributes to its unique surface properties. In addition, transmission electron microscopy (TEM) mapping showed that C, N, and O elements were uniformly distributed on the surface of CN-AQ-3, while Cl elements were scattered around. The high-resolution electron microscopy image of CN-AQ-3 identified lattice fringes with spacings of 0.345nm and 0.659nm, corresponding to the (100) and (002) lattice fringes of g-C3N4, respectively. The same obvious diffraction rings were also observed in the figure, indicating that the CN-AQ-3 sample has a more ordered structure and higher crystal integrity. The high crystal integrity of CN-AQ-3 may be attributed to the rearrangement of the g-C3N4 structural units during the binding process with the anthraquinone group. The ordered structure and thinner nanosheet structure of CN-AQ-3 may facilitate the flow of photogenerated charges.
[0130] Figure 4 The photocatalytic performance of the photocatalyst was evaluated by measuring the production of hydrogen peroxide (H2O2) under visible light irradiation (λ<400nm). Figure 4 ). During the 8h test period, the oxidatively modified photocatalyst CN-AQ-3 showed the best photocatalytic performance because the introduced C-OH edge was better able to bind to AQ-COOH and successfully combined the AQ molecular fragment. This simultaneously enhanced the separation efficiency of photocarriers and expanded the response range of photocatalytic performance. The H2O2 production of CN-AQ-3 increased significantly to 4.03wt%.
[0131] Comparative Example 1
[0132] Catalyst preparation:
[0133] Step (1): 10 g of melamine was placed in a quartz boat, placed in a tube furnace at room temperature, heated to 550° C. at a rate of 3° C. / min, kept at this temperature for 3 h, and then cooled to room temperature to obtain 2 to 3 g of carbon nitride CN-1;
[0134] Step (2): The carbon nitride CN-1 sample is reacted with 0.2 mmol of a chlorination reagent (such as ferrous chloride, ethyl chloride, methyl chloride) in 20 ml of acetonitrile solvent. The reaction conditions are temperature (20-60° C.), time (10-16 h) and Ph 8-10, and the reaction is carried out under an inert atmosphere of N2 to prevent the chlorination reagent from volatilizing or being affected by water or oxygen in the outside air, and a mixture suspension is obtained.
[0135] Step (3): add 2 mmol AQ-OH to the mixture suspension obtained in step (2), continue stirring at room temperature for 24 hours, filter and dry to obtain the AQ-CN-1 sample, and after the reaction is completed, use a centrifuge at a speed of 1200 r / min for 15 minutes, and then vacuum dry the lower layer of solid at 0.04 kPa and 60° C. to obtain the CN-AQ-1 sample of visible light catalyst comparative example 1;
[0136] Step (4): Mix 3 ml of ethanol and 10 mg of visible light catalyst CN-AQ-1, and after adsorption equilibrium for 2 hours in a saturated oxygen atmosphere at 25°C, react in a photoreactor under 10 W white light irradiation while maintaining the reaction temperature at 25°C for 8 hours. Centrifuge the obtained reaction solution at 1200 r / min for 10 minutes, take the supernatant and calibrate it by iodine titration. The concentration of hydrogen peroxide H2O2 is 0.17 wt%.
[0137] Comparative Example 2:
[0138] Catalyst preparation:
[0139] Step (1): 10 g of melamine was placed in a quartz boat, placed in a tube furnace at room temperature, heated to 550° C. at a rate of 3° C. / min, kept at this temperature for 3 h, and then cooled to room temperature to obtain 2 to 3 g of carbon nitride CN-2;
[0140] Step (2): The surface of the carbon nitride CN-2 is treated with ammoniation using 1 mmol of isopropylamine solution and 20 ml of ethanol solvent, and stirred at 30-50°C for 6-12 hours to obtain a CN-NH2 mixture suspension sample modified with a large number of amino functional groups.
[0141] Step (3): Under acidic conditions with a pH of 4-6, the mixture suspension CN-NH2 obtained in step (2) is mixed with 2mmolAQ-NH2, 0.5mmol of cross-linking agent polyethylene glycol, 0.2mmol of catalyst benzoyl peroxide and 20ml of dichloromethane solvent are added, and stirred for 8-16h at a temperature of 20-50°C. The reaction atmosphere is air. After the reaction is completed, a centrifuge is used at a speed of 1200r / min. After centrifugation for 15min, the lower layer of solid is vacuum dried at 0.04kPa and 60°C to obtain the CN-AQ-2 sample of visible light catalyst comparative example 2;
[0142] Step (4): Mix 3 ml of ethanol and 10 mg of visible light catalyst CN-AQ-2, and after adsorption equilibrium for 2 hours in a saturated oxygen atmosphere at 25°C, react in a photoreactor under 10 W white light irradiation while maintaining the reaction temperature at 25°C for 8 hours. Centrifuge the obtained reaction solution at 1200 r / min for 10 minutes, take the supernatant and calibrate it by iodine titration. The concentration of hydrogen peroxide H2O2 is 0.08 wt%.
[0143] Comparative Example 3:
[0144] Catalyst preparation:
[0145] Step (1): 10 g of melamine was placed in a quartz boat, placed in a tube furnace at room temperature, heated to 550° C. at a rate of 3° C. / min, kept at this temperature for 3 h, and then cooled to room temperature to obtain 2 to 3 g of carbon nitride CN-3;
[0146] Step (2): The surface of the carbon nitride CN-2 is treated with ammoniation using 1 mmol of isopropylamine solution and 20 ml of ethanol solvent, and stirred at 30-50°C for 6-12 hours to obtain a CN-NH2 mixture suspension sample modified with a large number of amino functional groups.
[0147] Step (3): Mix the mixture suspension CN-NH2 obtained in step (2) with 2mmol AQ-COOH, add 0.5mmol of condensation agent N,N'-dicyclohexylcarbodiimide (DCC), 0.2mmol of 4-dimethylaminopyridine (DMAP) catalyst and 20ml of dichloromethane solvent, stir for 24h at a temperature of 20-30°C, the reaction atmosphere is air, and after the reaction is completed, centrifuge at a speed of 1200r / min for 15min, and then vacuum dry the lower layer of solid at 0.04kPa and 60°C to obtain the CN-AQ-3 sample of visible light catalyst comparative example 3;
[0148] Step (4): Mix 3 ml of ethanol and 10 mg of visible light catalyst CN-AQ-3, and after adsorption equilibrium for 2 hours in a saturated oxygen atmosphere at 25°C, react in a photoreactor under 10 W white light irradiation while maintaining the reaction temperature at 25°C for 8 hours. Centrifuge the obtained reaction solution at 1200 r / min for 10 minutes, take the supernatant and calibrate it by iodine titration. The concentration of hydrogen peroxide H2O2 is 0.23 wt%.
[0149] Comparative Examples 4 and 5
[0150] References 6 and 7 in the background technology
[0151] Comparative Examples 1-5 illustrate the bonding methods of other AQ derivatives and carbon nitride. Through the analysis of the above comparative examples 1-5, it can be seen that the H2O2 concentrations of the above methods are 0.17wt%, 0.08wt%, 0.23wt%, 0.32mmol g, respectively. -1 h -1 、60mmol g -1 h -1 It can be seen that the use of non-amide bond bonding methods or organic synthesis methods other than those in this patent cannot construct a covalent bonding structure between carbon nitride and anthraquinone, thereby significantly improving the production of hydrogen peroxide. In short, none of the comparative examples 1-6 is as effective as the amide bond bonding method described in Examples 1-6 of the present invention.
[0152] Figure 5 Compared with the CN-B-AQ sample, the H2O2 yield of the CN-AQ sample formed under air conditions was 1.54wt%, the CN-GO sample lacking anthraquinone molecules only produced 0.15wt%, and the T-CN sample that did not fully form a carbon nitride structure had a H2O2 yield of 1.34wt%. The H2O2 concentrations of these three control experiments were all lower than that of CN-B-AQ (2.56wt%), indicating that the excellent hydrogen peroxide yield of CN-B-AQ originated from the organic bonding of anthraquinone molecules and the introduction of oxygen functional groups (carbonyl, C=O) into the carbon nitride structure. The factors introduced by changing the synthesis atmosphere conditions (O2) jointly promoted the efficient synthesis of H2O2, and each factor played an indispensable role. The H2O2 production of the two control samples of CN+AQ-COOH and CN+AQ obtained directly by physical mixing was 0.7wt% and 0.82wt%, indicating that the catalyst obtained by organic covalent bonding reaction of CN-B-AQ sample has a significant effect in increasing H2O2 production.
[0153] Figure 6The modification methods of the catalyst sample CN-3 obtained in step 1 of Example 3 are compared. Compared with the commonly reported carbon nitride modification methods of mixed salt co-dissolution method, metal ion doping method, and mixed pyrolysis of other types of precursors with NH4Cl, the CN-3 sample has the highest hydrogen peroxide yield, which is the best catalyst sample in the experimental condition screening, paves the way for the next oxidation reaction, and is also conducive to covalent bonding with anthraquinone molecules to further obtain a photocatalyst sample with better performance.
[0154] It should be understood that the above embodiments are only used to explain the technical solutions of the present invention, and are not intended to limit the scope of the present invention. Those skilled in the art can make various modifications, changes and equivalent substitutions based on the above description, and these modifications, changes and equivalent substitutions all fall within the scope of protection defined by the claims attached to the present invention. All features, elements or steps mentioned in the present invention should be deemed non-essential unless explicitly indicated as necessary. Any content that is not specifically pointed out as a key component or step in the claims should not be construed as limiting the scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the attached claims and their equivalents, and should not be limited to the specific implementation methods given in the aforementioned description.
Claims
1. A method for preparing a visible light catalyst based on bonding of carbon nitride and anthraquinone, characterized in that: The composite organic semiconductor catalyst comprises a graphite phase semiconductor carbon nitride and an anthraquinone compound bonded by an amide or ester chemical bond, and the specific preparation method is as follows: Step (1): using at least one of dicyandiamide, melamine, thiourea, urea, ammonium thiocyanate, ammonium thiocyanate and ammonium sulfate, ammonium thiocyanate and ammonium thiosulfate, ammonium thiocyanate, ammonium thiosulfate and ammonium sulfate as a precursor; heating at normal pressure, with the heating rate controlled at 2 to 20°C / min, the temperature is increased to 450 to 650°C, and maintained for 1 to 5 hours to obtain a graphite phase semiconductor carbon nitride having an edge amino group or a cyano group; Wherein, in the case of obtaining edge cyano groups, additional ammonium chloride is added and physically ground and mixed with the above precursor; Step (2): In the case of forming an ester chemical bond, the g-C3N4 containing a cyano group obtained in step (1) is additionally subjected to an oxidative modification treatment to convert it into a hydroxyl group; Step (3): converting the anthraquinone compound containing a carboxylic acid, carboxylic acid ester or amide substituent into an anthraquinone compound containing an acyl halide functional group; Step (4): according to the selected chemical bond type, the graphite phase semiconductor carbon nitride containing amino groups directly obtained in step (1) or the graphite phase semiconductor carbon nitride containing hydroxyl groups after oxidation modification in step (2) is respectively mixed with the anthraquinone compound containing acyl halide functional groups obtained in step (3), in the presence of an organic base or an inorganic base acid-binding agent, at normal pressure of 10 to 60° C. and oxygen atmosphere for 1 to 24 hours; separated, washed and dried to obtain the final product.
2. The preparation method according to claim 1, characterized in that: In step (2), the oxidation catalyst in the oxidation modification process includes: citric acid with a concentration of 0 to 1.5 eq and at least one of the following: hydrogen peroxide, ammonium persulfate, ammonium iodate, perchloric acid and benzoyl peroxide with a concentration of 1 to 2 eq.
3. The preparation method according to claim 1, characterized in that: In step (3), the anthraquinone compound containing carboxylic acid, carboxylic acid ester, or amide substituent is selected from the following: anthraquinone-1-carboxylic acid, anthraquinone-2-carboxylic acid, anthraquinone-2,6-dicarboxylic acid, anthraquinone-2,3-dicarboxylic acid, 4,5-dicarboxyanthraquinone, 1,4-anthraquinone-2,3-dicarboxylic acid; 4,5-dihydroxyanthraquinone-2-carboxylic acid, 1-aminoanthraquinone-2-carboxylic acid, anthraquinone-2,3-dicarboxylic acid diethyl ester, 4,5-diacetylanthraquinone, 4,5-diamideanthraquinone, and 1,4-anthraquinone-2,3-diamide.
4. The preparation method according to claim 1, characterized in that: In step (3), the anthraquinone compound containing an acyl halide functional group is prepared by using an acyl halide reagent selected from the following: thionyl chloride, oxalyl chloride, phosphorus trichloride, phosphorus oxychloride at a concentration of 1 to 2 eq; pyridine or 4-dimethylaminopyridine at a concentration of 0.1 to 0.2 eq is added during the process, and the reaction is carried out at normal pressure and a temperature of 10 to 60°C.
5. The preparation method according to claim 1, characterized in that: In step (4), the inorganic alkaline acid-binding agent is selected from one of the following: ammonia water, sodium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide; the organic alkaline acid-binding agent is selected from one of the following: triethylamine, ammonium acetate, acetamide, phenylethylamine hydrochloride, N,N-diisopropylethylamine, N,N-dimethylformamide, N,N-dimethylacetamide.
6. A visible light photocatalyst based on bonding of carbon nitride and anthraquinone prepared by the method as claimed in claim 1.
7. Use of the catalyst as claimed in claim 6 in hydrogen peroxide production or wastewater treatment.
8. The use according to claim 7, characterized in that: The application in hydrogen peroxide production is characterized by comprising the following steps: taking 4 to 30 wt % of the visible light catalyst based on carbon nitride and anthraquinone bonding according to claim 1, mixing it with water and / or C2 to C6 low-carbon alcohol, and irradiating it with ultraviolet light or visible light at 15 to 45° C. in an oxygen atmosphere to produce hydrogen peroxide.
9. The use according to claim 8, characterized in that: The C2-C6 low-carbon alcohol is selected from one of methanol, ethanol, isopropanol, propanol, ethylene glycol and 1,2-propylene glycol.
10. The use according to claim 8, characterized in that: The mixing volume ratio of the water to the C2-C6 low-carbon alcohol is 0-1:1.
Citation Information
Patent Citations
Method for generating amido bond
CN101235078B
Preparation method of hydrogen peroxide
CN106829872B
Mesoporous silica materials, their preparation methods, and their applications in the preparation of hydrogen peroxide
CN109289839B
Anthraquinone process for preparing hydrogen peroxide: an oxidation method
CN111099563B
Nanocatalysts for the electrochemical preparation of hydrogen peroxide, their preparation methods and applications
CN111617775B